Reliability of Profile Photography for Determining Growth Pattern and Sagittal Jaw Relationship in Different Classes of Malocclusions - Prasanna T.R1 , Navaneethan.R2 , Sri Rengalakshmi3 , Prasanna Arvind T.R.4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Although the importance of facial photography has been stressed in literature, there are no studies on itsdiagnostic potential. This study was conducted to evaluate the diagnostic merit of photography in detectinggrowth patterns and jaw relationships. Standardized lateral cephalograms and profile photographs were takenfor 40 patients. On cephalometry, growth patterns and sagittal classifications were determined. Diagnosticphotography- based measurements for detecting departures from the norm were calculated according tothe gold standard (lateral cephalometry). Independent sample t-test was used for comparing mandibularplane angles with profile photography and with lateral cephalometry. The mean value of the mandibularplane angle as determined by lateral cephalometry is 30.27+4.59. The mean value of the mandibularplane angle as determined by profile photography is 31.80+4.76. There was no significant difference seen.Profile photography is equally reliable as lateral cephalometry in detecting mandibular plane angle. Profilephotography can be used as a perfectly accurate measurement tool for detecting horizontal and verticalgrowth patterns. It is also a rather accurate method for detecting normal growth patterns, as well as bothClass I and non-Class I jaw relationships. These results highlight this non-invasive and economic method asan effective diagnostic tool. There is good association between lateral cephalometry and profile photographyin detecting mandibular plane angle in different skeletal groups as well.